Global-scale remote sensing of mine areas and analysis of factors explaining their extent. (January 2020) - Werner, Tim T.; Mudd, Gavin M.; Schipper, Aafke M.; Huijbregts, Mark A.J.; Taneja, Lakshay; Northey, Stephen A.
Highlights: We produce maps of 295 mines which represent the majority of current Cu, Au, Ag, PGE, Mo, Pb-Zn, Ni, U and diamond production. We delineate pits, waste rock dumps, tailings storage facilities, infrastructure and water storage pond areas separately. We collate production, mine configuration, waste and topography data for 129 sites and use these to perform regressions that predict the area of mine features. The area of mine features can be estimated with reasonable uncertainty using cumulative production and mine configuration as predictors. Abstract: Mines are composed of features like open cut pits, water storage ponds, milling infrastructure, waste rock dumps, and tailings storage facilities that are often associated with impacts to surrounding areas. The size and location of mine features can be determined from satellite imagery, but to date a systematic analysis of these features across commodities and countries has not been conducted. We created detailed maps of 295 mines producing copper, gold, silver, platinum group elements, molybdenum, lead-zinc, nickel, uranium or diamonds, representing the dominant share of global production of these commodities. The mapping entailed the delineation and classification of 3, 736 open pits, waste rock dumps, water ponds, tailings storage facilities, heap leach pads, milling infrastructure and other features, totalling ~3, 633 km 2 . Collectively, our maps highlight that mine areas can be highly heterogeneous in composition and diverse in form, reflecting variations in underlying geology, commodities produced, topography and mining methods. Our study therefore emphasises that distinguishing between specific mine features in satellite imagery may foster more refined assessments of mine-related impacts. We also compiled detailed annual data on the operational characteristics of 129 mines to show via regression analysis that the sum area of a mine's features is mainly explained by its cumulative production volume (cross-validated R 2 of 0.73). This suggests that the extent of future mine areas can be estimated with reasonable certainty based on expected total production volume. Our research may inform environmental impact assessments of new mining proposals, or provide land use data for life cycle analyses of mined products.